Application of taguchi technique to surface-grinding of mold steel - (:unkn) unknown (Trans Tech Publications Ltd, 2016)
The selection of optimum machining parameters plays a significant role for the quality characteristics of products and its costs for grinding. This study describes the optimization of the grinding process for an optimal parametric combination to yield a surface roughness using the Taguchi method. An orthogonal array and analysis of variance are employed to investigate the effects of cutting environment (A), depth of cut (B) and feed rate (C) on the surface roughness characteristics of mold steels. Confirmation experiments were conducted to verify the optimal testing parameters. The experimental results indicated that the surface finish decreased with cutting-fluid and depth of cut, but decreased with increasing feed rate. It is revealed that the cutting fluid environment had highest physical as well as statistical influence on the surface roughness (71.38%), followed by depth of cut (25.54%), but the least effect was exhibited by feed rate (1.62%). © 2016 Trans Tech Publications, Switzerland.
Keywords: Cutting fluid; Depth of cut; Feed rate; Grinding; Mold steel; Surface roughness